World Investment Report 2012 - United Nations Conference on Trade; Development (United Nations, 2012)
This annual report is widely regarded as the most authoritative source of data and analysis on the trends of foreign direct investment and developments in related national and international policy. Every issue of the report comprises an analysis of the trends in foreign direct investment during the previous years with special emphasis on development implications. It also provides a ranking of the largest transnational corporations in the world, in-depth analysis of a specific topic related to foreign direct investment, policy analysis and recommendations, and a statistical annex with data on foreign direct investment flows and stocks for nearly 200 economies. The 2012 edition presents a comprehensive investment policy framework for sustainable development, covering both its national and international dimensions.